The Effect of Lumbar Spinal Muscle on Spinal Sagittal Alignment: Evaluating Muscle Quantity and Quality. Issue 6 (December 2016) - Jun, Hyo Sub; Kim, Ji Hee; Ahn, Jun Hyong; Chang, In Bok; Song, Joon Ho; Kim, Tae Hwan; Park, Moon Soo; Chan Kim, Yong; Kim, Seok Woo; Oh, Jae Keun; Yoon, Do Heum
Abstract : BACKGROUND: The majority of earlier studies of the parameters of sagittal balance did not consider the influence of spinal muscles on spinal sagittal alignment. OBJECTIVE: To analyze the relationship between the paraspinal muscle (quantity and quality) and sagittal alignment in elderly patients. METHODS: We reviewed 50 full-spine lateral standing radiographs and lumbar magnetic resonance images of elderly patients at a single center. The radiographic parameters examined were thoracic kyphosis, lumbar lordosis (LL), sagittal vertical axis, pelvic tilt, sacral slope, and pelvic incidence (PI). The lumbar muscularity (LM; quantity) and fatty degeneration ratio (FD; quality) in the paraspinal muscle were measured at the L3 level on magnetic resonance images. The relationships between the parameters, LM, and FD were analyzed with the Pearson correlation coefficient and multiple linear regression. RESULTS: Pearson analysis demonstrated that the FD had significant correlations with age ( r = 0.393), thoracic kyphosis ( r = −0.559), pelvic tilt ( r = 0.430), sagittal vertical axis ( r = 0.488), and PI − LL ( r = 0.479, P < .05), and a close negative correlation was found between the FD and LL ( r = −0.505, P < .01). The LM had significant correlations with the LL ( r = 0.342) and PI − LL ( r = −0.283, P < .05). Regression models that controlled for confounding factors such as body mass index confirmed the correlations between the above parameters and FD ( P < .05). CONCLUSION: The quality of the paraspinal muscle could be one of the various factors that influence sagittal balance. ABBREVIATIONS: BMI, body mass index CSA, cross-sectional area FD, fatty degeneration ratio LL, lumbar lordosis LM, lumbar muscularity PI, pelvic incidence PT, pelvic tilt SC, subcutaneous fat SS, sacral slope SVA, sagittal vertical axis TK, thoracic kyphosis VB, vertebral body